179k views
1 vote
Solve for j

-1/3 = j/4 - 10/3

Solve for j -1/3 = j/4 - 10/3-example-1
User NadavS
by
5.2k points

1 Answer

4 votes
Answer: J=12


Explanation: To make this equation easier to solve, you can make everything a whole number (a.k.a. Remove the fractions). To do so, you can multiply everything in this equation by the Least Common Multiple (LCM) of all the denominators, which is 12. The equation now becomes:

-4=3J-40

Then, solve it using normal algebra:

-4=3J-40
36=3J
J=12

Much easier, right?!



Hope that helps シ

User Renjith R
by
4.4k points